ASSESSMENTS FOR STUDENTS: TYPES, PURPOSES, AND BEST PRACTICES - Ergashova Feruza Yuldashevna (Bright Mind Publishing, 2025)
Assessment is a critical component of the educational process, serving as a primary mechanism for monitoring student learning, informing pedagogical decisions, and shaping educational policy. This article offers a comprehensive overview of the primary types of assessments employed in contemporary educational settings, including summative, formative, diagnostic, and performance-based assessments. It emphasizes the specific purposes each type serves within the instructional cycle and identifies best practices for their implementation to ensure valid, reliable, and equitable measurement of student learning outcomes. Additionally, the article discusses emerging challenges and opportunities in the context of technological integration and student diversity, providing evidence-based recommendations for future assessment strategies.
Keywords: Assessment, summative assessment, formative assessment, diagnostic assessment, authentic assessment, learning outcomes, feedback in education, educational measurement.